A new perspective of how to understand entropy in thermodynamics. (1st November 2019) - Wu, Guobin; Wu, Amy Yimin
Abstract: Using the analogy between thermodynamics and electricity, two new concepts of thermal charge and quantity of thermal charge are introduced. A simple yet explicit definition of entropy is then derived—entropy is the quantity of thermal charge. As a result, quantity of thermal charge (entropy) and quantity of heat (energy) are now clearly distinguishable from each other. The former is an energy carrier while the latter is energy itself. This largely eliminates the difficulties in learning and applying thermodynamics, and therefore will be of considerable assistance to those who work, teach and study in the fields associated with thermodynamics. This also leads us to re-examine the validity of caloric theory and make a brief comment on it.